2007
DOI: 10.1152/ajpregu.00328.2006
|View full text |Cite
|
Sign up to set email alerts
|

Role of glucocorticoid receptor in acclimation of killifish (Fundulus heteroclitus) to seawater and effects of arsenic

Abstract: Role of glucocorticoid receptor in acclimation of killifish (Fundulus heteroclitus) to seawater and effects of arsenic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
80
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(87 citation statements)
references
References 47 publications
7
80
0
Order By: Relevance
“…Despite these observations, the administration of either aldosterone or deoxycorticosterone in Atlantic salmon parr did not significantly alter the response of fish to a 24h seawater challenge (McCormick et al, 2008), and this lack of response is in agreement with a small number of additional studies that have similarly reported an absence of effect when considering a role for either aldosterone or deoxycorticosterone in salt and water balance in fish (Chan et al, 1967;Takahashi et al, 2006;Umminger and Gist, 1973). Nevertheless, studies have reported that the MR antagonist spironolactone can alter endpoints of osmoregulation in fish and that the effects of spironolactone can differ from the effects of the GR antagonist RU486 (Kiilerich et al, 2007;Scott et al, 2005;Shaw et al, 2007;Sloman et al, 2001).…”
Section: Introductionsupporting
confidence: 79%
“…Despite these observations, the administration of either aldosterone or deoxycorticosterone in Atlantic salmon parr did not significantly alter the response of fish to a 24h seawater challenge (McCormick et al, 2008), and this lack of response is in agreement with a small number of additional studies that have similarly reported an absence of effect when considering a role for either aldosterone or deoxycorticosterone in salt and water balance in fish (Chan et al, 1967;Takahashi et al, 2006;Umminger and Gist, 1973). Nevertheless, studies have reported that the MR antagonist spironolactone can alter endpoints of osmoregulation in fish and that the effects of spironolactone can differ from the effects of the GR antagonist RU486 (Kiilerich et al, 2007;Scott et al, 2005;Shaw et al, 2007;Sloman et al, 2001).…”
Section: Introductionsupporting
confidence: 79%
“…We found the CFTR signal almost exclusively in seawater-acclimated alewives. Similarly, higher acclimation salinity stimulated increased branchial CFTR transcript abundance in killifish (Singer et al, 1998) and Atlantic salmon [CFTRI (Singer et al, 2002;Nilsen et al, 2007)] and CFTR protein expression in killifish (Shaw et al, 2007) and sea bass (Bodinier et al, 2009). We conclude that CFTR functions in Cl -secretion in hypo-osmoregulating alewives.…”
Section: Discussionsupporting
confidence: 55%
“…The effect of cortisol on CFTR-I and CFTR-II levels in FWand SW gills was consistently abolished by RU486, indicating that cortisol signals through the GR in both hyper-and hypo-osmoregulating gill tissue. An inhibitory effect of RU486 was also shown for CFTR in the gill of SW-acclimating (Shaw et al 2007), but not FW-acclimating (Scott et al 2005) killifish. The present reduction of CFTR levels by RU486 alone when compared with control levels may be due to blocking of endogenous cortisol left in the tissue or due to a nonspecific effect of the antagonist.…”
Section: Regulation Of Cftr-i and Cftr-iimentioning
confidence: 84%
“…These antagonists have previously been employed in several fish studies (Sloman et al 2001, Bury et al 2003, Scott et al 2005, Shaw et al 2007) without appreciably unspecific effects. However, the limited use and the insufficient validation of specificity of the antagonists in fish systems might impute some uncertainty to the conclusions.…”
Section: Fig 5b) No Significant Effect Of Cortisol or Antagonists On Hmentioning
confidence: 99%